The “Made in Egypt” Label Effect on Egyptian Consumers’ Purchase Intention - Khela, Mirna Ibrahim (AUC Knowledge Fountain, 2023)
This study employed a survey to investigate the Country of origin (COO) effect of the “Made in Egypt” label on Egyptian consumers’ purchase intentions of products and services. By using the conjoint analysis, the study was able to test the purchase intention process. The study tested high durability, low durability, and service industry, with attributes (price, specs, and COO) and levels (within attributes). Respondents were given several combinations of those attributes and levels through the survey design. They were asked to trade off the least important attributes for the most important ones to reach a final purchase decision. Previous studies have used the conjoint analysis technique to test the impact of COO on consumers’ purchase intention in developed countries. This study aims to test the impact on developing countries like Egypt and Egyptian consumers. The “Made in Egypt” label was found to have a significant effect across all products and services tested. The study has found that the label “Made in Egypt” is one of the key variables affecting Egyptian consumer’s purchase intention specially in high durability products like Smartphones. In low durability products, like T-shirts Egyptian consumers made their purchase decision based on COO as well, however when the “Made in Egypt” product becomes cheaper than the imported products, most respondents traded- off COO for the cheaper price. For the service industry, Egyptian consumers had the COO as the most important and only important attribute. However with price elasticity, other product attributes became major determinants of product purchase, however COO was the one of the key attributes to choosing which delivery company to use